Integration of higher and secondary education: problems and ways of their solution on the basis of information technologies - Meteshkin, Kostiantyn; Sokolov, Oleksandr; Morozova, Olga; Teplova, Nataliya (Journal of Education, Health and Sport, 2016)
Meteshkin Kostiantyn, Sokolov Oleksandr, Morozova Olga, Teplova Nataliya. Integration of higher and secondary education: problems and ways of their solution on the basis of information technologies. Journal of Education, Health and Sport. 2016;6(7):375-390. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.58067 http://ojs.ukw.edu.pl/index.php/johs/article/view/3703 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2016. Revised 09.07.2016. Accepted: 15.07.2016. INTEGRATION OF HIGHER AND SECONDARY EDUCATION: PROBLEMS AND WAYS OF THEIR SOLUTION ON THE BASIS OF INFORMATION TECHNOLOGIES Kostiantyn Meteshkin1, Oleksandr Sokolov2, Olga Morozova3, Nataliya Teplova4 1Department of Geoinformation Systems, Estimation of Land and Real Estate, National University of Urban Economy, Marshal Bazhanov Street 17, 61002, Kharkiv, Ukraine E-mail: kometeshkin@yandex.ru 2Department of Informatics, Faculty of Physics, Astronomy and Informatics, Nicolaus Copernicus University, Grudzianska 5, 87-100, Torun, Poland E-mail: osokolov@islumk.pl 3Department of Theoretical Mechanics, Mechanical Engineering and Robotic Systems, National Aerospace University, Chkalov Street 17, 61070, Kharkiv, Ukraine E-mail: oligmorozova@gmail.com 4№ 105 Kharkiv comprehensive school of I-III level of Kharkiv City Council of Kharkiv region, Danilevsky Street 36, 61058, Kharkiv, Ukraine E-mail: natateplova7@gmail.com Abstract: Many of today's problems are related to state and efficiency of education system in the country. This article deals with the integration problem of higher and secondary education through creating information relationship between schools and higher educational institutions. The system analysis approach forms the basis of researches. These methods examine the crisis arising between higher and secondary school systems. Besides, systemic and synergistic approach is used. Its techniques help to identify signs of the change of methodological pedagogy paradigm to methodological educology paradigm. Entrants have complications while entering and choosing a higher educational institution and faculty. Cross-contradictions between two educational systems – higher educational institutions and secondary schools are studied. Keywords: methodology; paradigm; school; higher educational institution; information technologies.